The Development of Parent’s Education Rationalization Towards The Orientation to Choose English Department Of Faculty Of Letters In Higher Education - Sismudjito Sismudjito (Jurnal Pemberdayaan Komunitas, 2015)
Abstract Rationalization of parent’s education is an intended action thru meaningful consideration and thought to choose higher education institution. This rationale is based on the data derived from many information resources which can predict many future possibilities before it comes to a decision. New orientation is as a change of self conception and parent’s education rationalization in giving choice of many conventional options before a child enter English Department, of faculty of letters in higher education institution. Due to this, somebody’s action is usually based on the stipulated objective, interest and motivation or may be by both. Children’s interest in this case, gives intrinsic motivation for themselves. Thus, orientation in choosing higher education of faculty of letters, English Department can be happened because of the rationalization influence of parent’s education and communication. Key words : Rationalization, communication and interest to choose in higher education